CXCL7-induced macrophage infiltration in lung tumor is independent of CXCR2 expression: CXCL7-induced macrophage chemotaxis in LLC tumors. Issue 2 (October 2015) - Unver, Nese; Esendagli, Gunes; Yilmaz, Guldal; Guc, Dicle
Highlights: Macrophage infiltration was increased in CXCL7-overexpressing LLC tumors. Increased macrophage infiltration was independent of CXC receptor 2 (CXCR2). The overexpression of the CXCL7 chemokine induced M2-type macrophage infiltration. Accelerated tumor growth was detected in CXCL7-overexpressing tumors. The infiltration of T-cell subsets did not change in CXCL7-LLC tumors. Abstract: Chemokines play diverse roles in modulating the immune response during tumor development. Levels of CXC chemokine ligand 7 (CXCL7) protein vary during tumorigenesis, and the evidence suggests that this chemokine serves as a novel biomarker of early-stage lung cancer. We investigated the effect of CXCL7 gene expression on the infiltration of myeloid cells into the tumor microenvironment in Lewis lung carcinoma (LLC). Tumors established from LLC cells overexpressing CXCL7 (CXCL7-LLC tumors) increased the infiltration of CD206 + M2 macrophages at the early stages of tumorigenesis. This infiltration was independent of CXCR2 expression on either tumor cells or macrophages. CXCL7-LLC tumors developed faster than control-LLC tumors (IRES-LLC tumor) did. The extent of CD4 + T cell, CD8 + T cell, and natural killer T cell infiltration was similar between the two tumor groups. Our findings suggest that CXCL7 attracts macrophages especially at the tumor site and may accelerate lung tumor development in the early stages.